Mitos Youkai Dalam Manga Natsume Yuujinchou Karya Yuki Midorikawa - Imelda Sasiandari, Ni Putu Ayu; Laksmita Sari, Ida Ayu; Indra Pradhana, Ngurah (Humanis, 2016)
This study entitled is “Youkai myth in Natsume Yuujinchou comic by Yuki Midorikawa”. This comic was choosed as a data source because there are some many related things about youkai and the functions of myth in it. The aim of this study are to determine the myths of Japanese people about youkai and myth’s function. Descriptive analysis method and informal method are used in this study. The used theories were literary anthropology by Endraswara (2008), functionalism theory by Boscom (2009) and semiotic theory by Danesi (2012). The results of this study are myth about youkai are derived from kami (God), myth about youkai can be sealed and myth about youkai’s habitation. Then, there are four myth’s function such as human projective system, as validiting culture, as pedagogical device, and applying social pressure and excercising social control.